2020
DOI: 10.1051/0004-6361/201936364
|View full text |Cite
|
Sign up to set email alerts
|

Angular momentum profiles of Class 0 protostellar envelopes

Abstract: Context. Understanding the initial properties of star forming material and how they affect the star formation process is a key question. The infalling gas must redistribute most of its initial angular momentum inherited from prestellar cores before reaching the central stellar embryo. Disk formation has been naturally considered as a possible solution to this "angular momentum problem". However, how the initial angular momentum of protostellar cores is distributed and evolves during the main accretion phase an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
88
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(109 citation statements)
references
References 172 publications
(303 reference statements)
20
88
1
Order By: Relevance
“…Recent analysis have revealed a more complex interpretation, with sources showing shifts or even reversal of the gas velocity gradients within envelopes. In some sources, the observed gradients might actually originate from on-going infall, or linked with turbulence (Gaudel et al 2020). In all cases however, large velocity gradients are tracing more dynamical envelopes with larger kinetic energy.…”
Section: Kinematic Properties Of the Protostellar Envelopesmentioning
confidence: 98%
See 3 more Smart Citations
“…Recent analysis have revealed a more complex interpretation, with sources showing shifts or even reversal of the gas velocity gradients within envelopes. In some sources, the observed gradients might actually originate from on-going infall, or linked with turbulence (Gaudel et al 2020). In all cases however, large velocity gradients are tracing more dynamical envelopes with larger kinetic energy.…”
Section: Kinematic Properties Of the Protostellar Envelopesmentioning
confidence: 98%
“…For sources that are part of the CALYPSO sample (i.e. L1157, L1448C, L1448N-B, L1448-2A, IRAS4A, IRAS4B and SVS13-B), Gaudel et al (2020) recently presented observations of the dense gas kinematics using C 18 O and N 2 H + measurements and derive specific angular momentum estimates throughout their collapsing protostellar envelopes from 50 au to 10 000 au scales. In their analysis, velocity maps are produced from a combined Plateau de Bure (PdBI) + 30-m N 2 H + dataset.…”
Section: Kinematic Properties Of the Protostellar Envelopesmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that RSDs also form because subsonic turbulence quickly develops and, angular momentum with respect to the moving star, is induced by the inertia forces. Therefore, the formation of initial disks can be a local process (∼10 3 au scale; see Gaudel et al 2020) and may not require organized rotation on the very large scale cloud (∼10 4 au).…”
Section: • the Role Of Turbulencementioning
confidence: 99%